Analysis of methane (CH4) and nitrous oxide (N2O) emission from paddy rice using IoT and fuzzy logic. (2nd December 2019) - Jadhav, Shriya A.; Lal, Anisha M.
The paper focuses on the analysis of methane (CH4 ) and nitrous oxide (N2 O) emission from paddy rice using IoT and fuzzy logic. The study of rice paddy fields brings out the fact that they are the substantial sources of greenhouse gases such as methane (CH4 ) and nitrous oxide (N2 O). Internet of thing provides an integrated solution for data acquisition, monitoring and measuring methane (CH4 ) and nitrous oxide (N2 O) concentration in air. The combination of IoT and fuzzy logic can be used in the development of intelligent system for pattern recognition, event prediction and decision making. Sensors deployed will provide real time data which will be pushed on centralized server where analysis is done for decision making using fuzzy logic. The researcher proposes a model which takes benefit of these technologies to monitor and analyze emission level of methane (CH4 ) and nitrous oxide (N2 O) from the rice paddy fields.